1987
DOI: 10.1104/pp.85.3.689
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fluence-Response Relationships of Phototropism in Light- and Dark-Grown Buckwheat

Abstract: Fluence-response relationships of phototropism in light-and darkgrown buckwheat (Fagopyrmn escukntum Moench.) were compared using systematically varied fluence rates and irradiation times of unilateral monochromatic blue light. Etiolated seedlings respond to most fluence rates in a tri-phasic manner. Phase one differs from classic first positive in that reciprocity is not observed and the peak occurs at a wide variety of fluences, often orders of magnitude less than those characteristic of first positive. Ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…In contrast with etiolated seedlings, Pringsheim (1912) observed that light-grown pea seedlings are more responsive to brighter light than to dimmer light. Similar behavior was observed in buckwheat (Ellis, 1987) and Arabidopsis (Whippo and Hangarter, 2005). However, how this developmental shift in phototropic sensitivity occurs is currently unknown.…”
Section: Toward Understanding Phototropism Sensitivity and Responsivesupporting
confidence: 56%
See 1 more Smart Citation
“…In contrast with etiolated seedlings, Pringsheim (1912) observed that light-grown pea seedlings are more responsive to brighter light than to dimmer light. Similar behavior was observed in buckwheat (Ellis, 1987) and Arabidopsis (Whippo and Hangarter, 2005). However, how this developmental shift in phototropic sensitivity occurs is currently unknown.…”
Section: Toward Understanding Phototropism Sensitivity and Responsivesupporting
confidence: 56%
“…However, von Wiesner also believed that the induction of phototropism was closely related to the induction of photomorphogenesis and concluded that the regulation of phototropic sensitivity and responsiveness coincides with light-mediated growth inhibition (von Wiesner, 1878). During the next century, Pringsheim (1912) and Ellis (1987) reconfirmed von Wiesner's initial observation, but a clear explanation of the phenomenon was not evident.…”
Section: Toward Understanding Phototropism Sensitivity and Responsivementioning
confidence: 86%
“…It is well known that a light pretreatment causes a shift in the fluence-response relationship (1,7,11,19) in the range of first positive curvature. The effect of ancymidol on the fluence-response curve is similar to that ofthe light pretreatment, a result that indicates that it might affect the photoreceptor system.…”
Section: Discussionmentioning
confidence: 99%
“…While this holds true for example for Phycomyces, which has a lower threshold for the bending rate after dark-growth than after light-growth (Galland and Russo, 1984b), the situation can be different in higher plants. The complex fluence-response curves for phototropism of buckwheat (Fagopyrum esculentum) vary considerably with preceding darkor light-growth (Ellis, 1987). In the low-fluence range dark-grown specimens have a lower threshold and react more strongly than light-grown ones.…”
Section: Influence Of Dark-and Light-growth On Sensitivitymentioning
confidence: 99%
“…In the low-fluence range dark-grown specimens have a lower threshold and react more strongly than light-grown ones. In the high-fluence range, on the other hand, lightgrown seedlings are more sensitive (Ellis, 1984(Ellis, , 1987. The different growth conditions not only influence the threshold (sensitivity) but also the adaptation kinetics.…”
Section: Influence Of Dark-and Light-growth On Sensitivitymentioning
confidence: 99%